Chagas disease-related mortality in Colombia from 1979 to 2018: temporal and spatial trends. - Mario Javier Olivera; Julián Felipe Porras-Villamil; Juan Carlos Villar; Eliana Váquiro Herrera; Giancarlo Buitrago (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract INTRODUCTIOn: Studies on Chagas disease-related mortality assist in decision-making in health policies. We analyzed the epidemiological characteristics, temporal trends, and regional differences in Chagas disease-related mortality in Colombia from 1979 to 2018. METHODS: A time-series study was conducted using death records and population data from the National Administrative Department of Statistics, using categorizations from the International Classification of Disease (ICD)-9 and ICD-10 systems. All deaths with Chagas disease as an underlying or associated cause of death were included. Crude and age-sex standardized mortality rates per 100,000 inhabitants and the annual percent change (APC) were calculated. RESULTS: Of the 7,287,461 deaths recorded in Colombia during 1979-2018, 3,276 (0.04%) deaths were related to Chagas disease-2,827 (86.3%) as an underlying cause and 449 (13.7%) as an associated cause. The average annual age-sex standardized mortality rate was 0.211 (95% confidence interval [CI]: 0.170-0.252) deaths/100,000 inhabitants, with a significant upward trend (APC = 6.60%; 95% CI: 5.9-7.3). The highest Chagas disease-related death rates were in males (0.284 deaths/100,000 inhabitants), those ≥65 years old (1.296 deaths/100,000 inhabitants), and residents of the Orinoco region (1.809 deaths/100,000 inhabitants). There was a significant increase in mortality in the Orinoco (APC = 8.28%; 95% CI: 6.4-10.2), Caribbean (APC = 5.06%; 95% CI: 3.6-6.5), and Andean (APC = 4.63%; 95% CI: 3.9-5.3) regions. CONCLUSIONS: Chagas disease remains a major public health issue in Colombia with high mortality rates in older age groups, a wide geographic distribution, regional differences, and the potential to increase.